(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2014)
hermal denaturing of human hemoglobin (HHb) in the presence of tannic acid (TA) was studied by fluorescence and UV/vis spectroscopy in 30–66°C temperature range. To study more detailed structural changes in HHb molecule caused by temperature rise in the presence of TA, the excitation/emission fluorescence (3D spectra) matrix method has been used. It has been shown, that the increase of temperature causes more pronounced structural changes in the flexible areas of protein containing aromatic amino acids than in the rigid α, β polypeptide chains. It was revealed that the presence of TA causes structural changes in HHb.